Wear-resistant nylon composite material and production method thereof
By optimizing the raw material formula and production process of nylon composite materials, the composite of aromatic polyamide, polysebabyl hexanediamine, polyisophthalyl m-phenylenediamine and linear polyethylene with polyphenylenediamine structure was solved The problem of insufficient wear resistance and mechanical strength of nylon composite materials has achieved the preparation of high-performance wear-resistant nylon composite materials, which is suitable for high-end fields.
Patent Information
- Application Number
- CN202411555138.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-10
AI Technical Summary
The existing nylon composite materials have shortcomings in wear resistance and mechanical strength, resulting in short service life and low reliability of the material. The production process has problems such as uneven melt blending and unstable granulation quality, which limits its high-end fields. application.
21-24 parts by mass of the aromatic polyamide in the polyphenylene ether structure, 15-18 parts by mass of polysebabyl hexanediamine, 7-10 parts by mass of polyisophthalyl m-phenylenediamine, 4- 6 parts by mass of UPE powder and 5-8 parts by mass of linear polyethylene, high-performance polyamide resin and aramid fiber were synthesized by a one-pot polycondensation method, and melt blended in a twin-screw extruder, and then passed Cooling, pelletizing, reinforcement and flame retardant modification treatments, and finally a wear-resistant nylon composite material is prepared by injection molding and blow molding processes.
It significantly improves the wear resistance, mechanical strength and flame retardant properties of nylon composite materials, improves the performance and quality of materials, and can be widely used in high-end fields.
Smart Images

Figure CN119286241A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, in particular to a wear-resistant nylon composite material and a production method thereof. Background Art
[0002] Although existing nylon composite materials have been widely used in many fields, such as automobile manufacturing, aerospace, electronic products, etc., their light weight, high strength and corrosion resistance have brought significant convenience to these fields. However, with the continuous advancement of industrial technology and the continuous expansion of application fields, the performance requirements for nylon composite materials are becoming higher and higher. At present, the raw material formula and production process of many nylon composite materials are not mature enough, which leads to deficiencies in wear resistance and mechanical strength of composite materials.
[0003] Specifically, some nylon composite materials are prone to wear, deformation, and even breakage when used for a long time or under heavy loads. This not only affects the service life and reliability of the material, but also limits its application in high-end fields. In addition, there are also some problems in the production process of some nylon composite materials, such as uneven melt blending and unstable granulation quality, which will directly affect the performance of the final product.
[0004] Therefore, in view of the low wear resistance and mechanical strength of existing nylon composite materials, it is necessary to conduct in-depth research and improve their raw material formula and production process. By optimizing raw material selection, adjusting formula ratio, improving melt blending and granulation process, nylon composite materials with better performance can be prepared. At the same time, strengthening quality control and testing is also the key to ensure product quality and stability. Only by continuously improving the performance and quality of nylon composite materials can we meet the growing market demand and challenges in application fields. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a wear-resistant nylon composite material and a production method thereof, which has the advantages of high wear resistance and high mechanical strength, and solves the problems of low wear resistance and mechanical strength of the composite materials in the prior art.
[0007] (II) Technical solution
[0008] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 21-24 weight parts of aromatic polyamide with a polyphenylene ether structure; 15-18 weight parts of polyhexamethylene sebacamide; 7-10 weight parts of polyisophthalamide; 4-6 weight parts of UPE micropowder; and 5-8 weight parts of linear polyethylene.
[0009] Preferably, the composite material is obtained by compounding a high-performance polyamide resin, aramid fibers and ultra-high molecular weight polyethylene particles, wherein the high-performance polyamide resin is composed of aromatic polyamide and polyhexamethylene sebacamide of a polyphenylene ether structure, the aramid fibers are polyisophthalamide, and the ultra-high molecular weight polyethylene particles are composed of UPE micropowder and linear polyethylene.
[0010] Preferably, the synthesis process of the aromatic polyamide with polyphenylene ether structure is:
[0011] S1.1. Raw material preparation: amino-terminated polydimethylsiloxane and polyphenylene ether are used as raw materials;
[0012] S1.2, one-pot polycondensation synthesis: amino-terminated polydimethylsiloxane and polyphenylene ether are polymerized by a one-pot polycondensation method to form an aromatic polyamide containing siloxane segments and polyphenylene ether structures;
[0013] S1.3. Synthesis conditions: Use a high-pressure reactor as the reaction equipment, and set the reactor temperature between 200-250°C.
[0014] Preferably, the purification process of the poly(m-phenylene isophthalamide) is as follows:
[0015] S2.1, adding m-phenylenediamine into an amide polar organic solvent at a temperature of 55-60°C;
[0016] S2.2, adding isophthaloyl chloride, and carrying out polymerization reaction at a temperature of 25-30°C to generate polyisophthaloyl chloride metaphenylenediamine condensation product and by-product hydrogen chloride;
[0017] S2.3. Add alkaline earth metal oxide and hydrogen chloride at a temperature of 25-30°C to react for 30-45 minutes to remove the by-product hydrogen chloride. After the reaction is completed, continue to add diethylamine to neutralize the remaining hydrogen chloride to finally obtain purified poly(m-phenylene isophthalamide).
[0018] Preferably, the production method of the wear-resistant nylon composite material is prepared according to the mass parts of the raw materials of the above-mentioned wear-resistant nylon composite material, and the preparation steps are:
[0019] Step 1, vacuum drying treatment: vacuum drying the aromatic polyamide of polyphenylene ether structure, polyhexamethylene sebacamide, polyisophthalamide, UPE micropowder and linear polyethylene;
[0020] Step 2, premixing: premix the dried raw materials in a ratio of 21-24:15-18:7-10:4-6:5-8;
[0021] Step 3, melt blending: adding the pre-mixed raw material mixture into a twin-screw extruder for melt blending;
[0022] Step 4: Granulation: The raw material mixture after melt blending is extruded through the die head of the extruder, cooled by a cooling device, and cut into granular materials by a pelletizer;
[0023] Step 5: Post-processing: secondary drying and screening of the granulated granular material, followed by enhancement and flame retardant modification;
[0024] Step 6: Molding: The modified granular material is processed into a nylon composite material through injection molding, extrusion and blow molding.
[0025] Preferably, the vacuum drying treatment conditions in step 1 are: the vacuum temperature is set to 85-90° C., and the vacuum drying time is set to 12-13 h.
[0026] Preferably, the premixing conditions in step 2 are: setting the speed of the high-speed mixer to 200-300 r / min, and setting the duration of the high-speed mixer to 15-20 min.
[0027] Preferably, the conditions for melt blending in step three are set as follows: the temperature of the twin-screw extruder is 250-300°C, the screw speed is 400-450r / min, the feeding rate is 30-45kg / h, and cooling, filtering, online monitoring and online adjustment equipment are additionally provided.
[0028] Preferably, the cooling device in step 4 is a cooling water tank, and the water inlet temperature of the cooling water tank is set at 20-30°C, and the water outlet temperature is controlled at 40-50°C.
[0029] Preferably, the reinforcement and flame retardant modification process in step five is: adding nano-glass fiber and nano-carbon fiber in a mass ratio of 1:6 to the granular material, and adding 3-5 mass parts of flame retardant to the granular material.
[0030] Compared with the prior art, the present invention provides a wear-resistant nylon composite material and a production method thereof, which has the following beneficial effects:
[0031] 1. The present invention forms a material with excellent wear resistance and mechanical strength by compounding high-performance polyamide resin, aramid fiber and ultra-high molecular weight polyethylene particles, and optimizing the preparation steps, including adding nano-glass fiber and nano-carbon fiber in a weight ratio of 1:6 to the modified granular material, and adding 3-5 weight parts of flame retardant to the granular material. The optimized formula and preparation method can not only improve the strength and rigidity of the nylon composite material, but also improve its wear resistance and flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1A flow chart was prepared for the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] See also Figure 1 , wear-resistant nylon composite material, the raw materials of the composite material and their weight parts are: 21-24 weight parts of aromatic polyamide with polyphenylene ether structure; 15-18 weight parts of polyhexamethylene sebacamide; 7-10 weight parts of polyisophthalamide; 4-6 weight parts of UPE micropowder; 5-8 weight parts of linear polyethylene.
[0035] Specifically, the composite material is obtained by compounding high-performance polyamide resin, aramid fiber and ultra-high molecular weight polyethylene particles. The high-performance polyamide resin is composed of aromatic polyamide with a polyphenylene ether structure and polyhexamethylene sebacamide, the aramid fiber is polyisophthalamide, and the ultra-high molecular weight polyethylene particles are composed of UPE micropowder and linear polyethylene.
[0036] Specifically, the synthesis process of aromatic polyamide with polyphenylene ether structure:
[0037] S1.1. Raw material preparation: amino-terminated polydimethylsiloxane (ATPDMS) and polyphenylene ether (PPO) are used as raw materials;
[0038] S1.2, one-pot polycondensation synthesis: amino-terminated polydimethylsiloxane and polyphenylene ether are polymerized by a one-pot polycondensation method to form an aromatic polyamide containing siloxane segments and polyphenylene ether structures;
[0039] S1.3. Synthesis conditions: Use a high-pressure reactor as the reaction equipment, and set the reactor temperature between 200-250°C.
[0040] Specifically, the purification process of poly(m-phenylene isophthalamide):
[0041] S2.1, adding m-phenylenediamine into an amide polar organic solvent at a temperature of 55-60°C;
[0042] S2.2, adding isophthaloyl chloride, and carrying out polymerization reaction at a temperature of 25-30°C to generate polyisophthaloyl chloride metaphenylenediamine condensation product and by-product hydrogen chloride;
[0043] S2.3. Add alkaline earth metal oxide and hydrogen chloride at a temperature of 25-30°C to react for 30-45 minutes to remove the by-product hydrogen chloride. After the reaction is completed, continue to add diethylamine to neutralize the remaining hydrogen chloride to finally obtain purified poly(m-phenylene isophthalamide).
[0044] Specifically, the production method of the wear-resistant nylon composite material is prepared according to the mass parts of the raw materials of the above-mentioned wear-resistant nylon composite material, and the preparation steps are:
[0045] Step 1: vacuum drying: vacuum drying the aromatic polyamide, polyhexamethylene sebacamide, poly(m-phenylene isophthalamide), UPE micropowder and linear polyethylene of the polyphenylene ether structure to remove moisture;
[0046] Step 2: Premixing: Premix the dried raw materials in a ratio of 21-24:15-18:7-10:4-6:5-8. This step can be performed using a high-speed mixer to ensure that the components are evenly dispersed.
[0047] Step 3, melt blending: adding the pre-mixed raw material mixture into a twin-screw extruder for melt blending;
[0048] Step 4: Granulation: The raw material mixture after melt blending is extruded through the die head of the extruder, cooled by a cooling device, and cut into granular materials by a pelletizer;
[0049] Step 5: Post-processing: The granulated material is subjected to secondary drying and screening to remove possible impurities and unqualified products, and then subjected to enhancement and flame retardant modification treatment;
[0050] Step 6: Molding: The modified granular material is processed into a nylon composite material through injection molding, extrusion and blow molding.
[0051] Specifically, the vacuum drying treatment conditions in step 1 are: the vacuum temperature is set to 85-90° C., and the vacuum drying time is set to 12-13 h.
[0052] Specifically, the premixing conditions in step 2 are: setting the speed of the high-speed mixer to 200-300 r / min, and setting the duration of the high-speed mixer to 15-20 min.
[0053] Specifically, the conditions for melt blending in step three are set as follows: the temperature of the twin-screw extruder is 250-300°C, the screw speed is 400-450r / min, the feeding rate is 30-45kg / h, and cooling, filtering, online monitoring and online adjustment equipment are added to ensure that the materials can be fully melted and mixed evenly.
[0054] Specifically, the cooling equipment in step 4 is a cooling water tank, and the water inlet temperature of the cooling water tank is set at 20-30°C, and the water outlet temperature is controlled at 40-50°C. Such temperature settings help ensure that the granular material can be quickly cooled and solidified after melt blending, thereby maintaining its good performance and quality.
[0055] Specifically, the reinforcement and flame retardant modification process in step five is: adding nano-glass fiber and nano-carbon fiber in a mass ratio of 1:6 to the granular material to improve the strength and rigidity of the material; adding 3-5 mass parts of flame retardant to the granular material to improve the flame retardant properties of the material.
[0056] Example 1
[0057] A wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 21 weight parts of aromatic polyamide with a polyphenylene ether structure; 15 weight parts of polyhexamethylene sebacamide; 7 weight parts of polyisophthalamide; 4 weight parts of UPE micropowder; and 5 weight parts of linear polyethylene.
[0058] Comparative Example 1
[0059] A wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 25 weight parts of polyhexamethylene sebacamide; 7 weight parts of poly(m-phenylene isophthalamide); 4 weight parts of UPE micropowder; and 5 weight parts of linear polyethylene.
[0060] Example 2
[0061] A wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 22 weight parts of aromatic polyamide with a polyphenylene ether structure; 16 weight parts of polyhexamethylene sebacamide; 8 weight parts of polyisophthalamide; 4 weight parts of UPE micropowder; and 5 weight parts of linear polyethylene.
[0062] Comparative Example 2
[0063] A wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 29 weight parts of aromatic polyamide with a polyphenylene ether structure; 8 weight parts of polyisophthalamide-m-phenylene diamine; 4 weight parts of UPE micropowder; and 5 weight parts of linear polyethylene.
[0064] Example 3
[0065] A wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 22 weight parts of aromatic polyamide with a polyphenylene ether structure; 16 weight parts of polyhexamethylene sebacamide; 9 weight parts of polyisophthalamide; 6 weight parts of UPE micropowder; and 7 weight parts of linear polyethylene.
[0066] Comparative Example 3
[0067] A wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 22 weight parts of aromatic polyamide with a polyphenylene ether structure; 16 weight parts of polyhexamethylene sebacamide; 9 weight parts of poly(m-phenylene isophthalamide); and 15 weight parts of linear polyethylene.
[0068] Example 4
[0069] A wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 22 weight parts of aromatic polyamide with a polyphenylene ether structure; 17 weight parts of polyhexamethylene sebacamide; 7 weight parts of polyisophthalamide; 4 weight parts of UPE micropowder; and 5 weight parts of linear polyethylene.
[0070] Comparative Example 4
[0071] A wear-resistant nylon composite material, wherein the raw materials of the composite material and their weight parts are: 22 weight parts of aromatic polyamide with a polyphenylene ether structure; 17 weight parts of polyhexamethylene sebacamide; 7 weight parts of poly(m-phenylene isophthalamide); and 14 weight parts of linear polyethylene.
[0072] The finished composite materials made from the raw materials of Examples 1-4 and Comparative Examples 1-4 were tested for mechanical properties, thermal properties, wear resistance and hardness. The test results are shown in Table 1:
[0073] Table 1
[0074]
[0075] Note: The value of wear resistance (mg / 1000 times) refers to the mass (in milligrams) lost by the material after 1000 times of friction or wear under specific conditions. The lower this value is, the less the material wears under the same conditions and the better its wear resistance is.
[0076] By comparing the test data of the embodiments and the comparative examples in Table 1, the composite materials in the embodiments are better than the corresponding comparative examples in terms of mechanical properties, thermal properties, wear resistance and hardness test results. Among them, Example 3 has the best performance test results in all aspects, with mechanical properties reaching 95MPa, thermal properties reaching 230°C, wear resistance of only 20mg / 1000 times, and hardness up to 85Shore D. Due to the adjustment of the raw material ratio in the embodiments: increasing the mass fractions of aromatic polyamide and polyisophthalamide metaphenylene diamine with a polyphenylene ether structure, and increasing the mass fraction of linear polyethylene, the continuous improvement and adjustment of the mass fractions of raw materials in the embodiments enables the composite material to maintain high strength while also improving heat resistance and wear resistance.
[0077] Example 5
[0078] The reinforcement and flame retardant modification process in step five is: adding nano-glass fiber and nano-carbon fiber in a mass ratio of 1:6 to the granular material to improve the strength and rigidity of the material; adding 4 mass parts of flame retardant to the granular material to improve the flame retardant properties of the material.
[0079] Comparative Example 5
[0080] The reinforcement and flame retardant modification process in step five is: adding glass fiber and carbon fiber in a mass ratio of 2:7 to the granular material to improve the strength and rigidity of the material; adding 4 mass parts of flame retardant to the granular material to improve the flame retardant properties of the material.
[0081] The finished composite materials made in Example 5 and Comparative Example 5 were tested for wear resistance and mechanical strength, and the results are shown in Table 2:
[0082] Table 2
[0083] project Example 5 Comparative Example 5 Wear resistance (mg / 1000 times) 25 30 Tensile strength(MPa) 98 90 Bending strength(MPa) 120 110 <![CDATA[Impact strength (kJ / m 2 )]]> 16 14 Flame retardant grade V-0 V-1
[0084] The following information can be obtained from Table 2:
[0085] Wear resistance: The wear resistance of Example 5 is better than that of Comparative Example 5, and its wear loss is lower, indicating that the addition of nano-glass fiber and nano-carbon fiber has a positive effect on improving the wear resistance of the material.
[0086] Mechanical strength: In terms of tensile strength, flexural strength and impact strength, Example 5 performs better than Comparative Example 5, thereby verifying the effectiveness of nano-scale reinforcement materials in improving the mechanical strength of composite materials.
[0087] Flame retardant properties: Example 5 reaches a flame retardant grade of V-0, while Comparative Example 5 is only V-1, indicating that the nano-glass fiber and nano-carbon fiber added in Example 5 can not only enhance the mechanical properties of the material, but also improve the flame retardant properties.
[0088] In summary, the modification process in Example 5 achieved excellent results in improving the wear resistance, mechanical strength and flame retardancy of the wear-resistant nylon composite material.
[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Wear-resistant nylon composite material, characterized in that: The raw materials of the composite material and their weight parts are: 21-24 weight parts of aromatic polyamide with polyphenylene ether structure; 15-18 weight parts of polyhexamethylene sebacamide; 7-10 weight parts of polyisophthalamide; 4-6 weight parts of UPE micropowder; and 5-8 weight parts of linear polyethylene.
2. The wear-resistant nylon composite material according to claim 1, characterized in that: The composite material is obtained by compounding high-performance polyamide resin, aramid fiber and ultra-high molecular weight polyethylene particles. The high-performance polyamide resin is composed of aromatic polyamide with a polyphenylene ether structure and polyhexamethylene sebacamide, the aramid fiber is polyisophthalamide, and the ultra-high molecular weight polyethylene particles are composed of UPE micropowder and linear polyethylene.
3. The wear-resistant nylon composite material according to claim 1, characterized in that: The synthesis process of the aromatic polyamide with polyphenylene ether structure: S1.
1. Raw material preparation: amino-terminated polydimethylsiloxane and polyphenylene ether are used as raw materials; S1.2, one-pot polycondensation synthesis: amino-terminated polydimethylsiloxane and polyphenylene ether are polymerized by a one-pot polycondensation method to form an aromatic polyamide containing siloxane segments and polyphenylene ether structures; S1.
3. Synthesis conditions: Use a high-pressure reactor as the reaction equipment, and set the reactor temperature between 200-250°C.
4. The wear-resistant nylon composite material according to claim 1, characterized in that: The purification process of the poly(m-phenylene isophthalamide) is as follows: S2.1, adding m-phenylenediamine into an amide polar organic solvent at a temperature of 55-60°C; S2.2, adding isophthaloyl chloride, and carrying out polymerization reaction at a temperature of 25-30°C to generate polyisophthaloyl chloride metaphenylenediamine condensation product and by-product hydrogen chloride; S2.
3. Add alkaline earth metal oxide and hydrogen chloride at a temperature of 25-30°C to react for 30-45 minutes to remove the by-product hydrogen chloride. After the reaction is completed, continue to add diethylamine to neutralize the remaining hydrogen chloride to finally obtain purified poly(m-phenylene isophthalamide).
5. A method for producing a wear-resistant nylon composite material, characterized in that: The wear-resistant nylon composite material according to claim 1 is prepared by the following steps: Step 1, vacuum drying treatment: vacuum drying the aromatic polyamide of polyphenylene ether structure, polyhexamethylene sebacamide, polyisophthalamide, UPE micropowder and linear polyethylene; Step 2, premixing: premix the dried raw materials in a ratio of 21-24:15-18:7-10:4-6:5-8; Step 3, melt blending: adding the pre-mixed raw material mixture into a twin-screw extruder for melt blending; Step 4: Granulation: The raw material mixture after melt blending is extruded through the die head of the extruder, cooled by a cooling device, and cut into granular materials by a pelletizer; Step 5: Post-processing: secondary drying and screening of the granulated granular material, followed by enhancement and flame retardant modification; Step 6: Molding: The modified granular material is processed into a nylon composite material through injection molding, extrusion and blow molding.
6. The method for producing the wear-resistant nylon composite material according to claim 5, characterized in that: The vacuum drying treatment conditions in step 1 are: the vacuum temperature is set to 85-90° C., and the vacuum drying time is set to 12-13 h.
7. The method for producing the wear-resistant nylon composite material according to claim 5, characterized in that: The premixing conditions in step 2 are: setting the speed of the high-speed mixer to 200-300 r / min, and setting the duration of the high-speed mixer to 15-20 min.
8. The method for producing the wear-resistant nylon composite material according to claim 5, characterized in that: The conditions for melt blending in step three are as follows: the temperature of the twin-screw extruder is 250-300° C., the screw speed is 400-450 r / min, the feeding rate is 30-45 kg / h, and cooling, filtering, online monitoring and online adjustment equipment are additionally provided.
9. The method for producing the wear-resistant nylon composite material according to claim 5, characterized in that: The cooling device in step 4 is a cooling water tank, and the water inlet temperature of the cooling water tank is set at 20-30°C, and the water outlet temperature is controlled at 40-50°C.
10. The method for producing the wear-resistant nylon composite material according to claim 5, characterized in that: The strengthening and flame retardant modification process in step five is: adding nano-glass fiber and nano-carbon fiber in a mass ratio of 1:6 to the granular material, and adding 3-5 mass parts of flame retardant to the granular material.